肺動脈性肺高血圧症におけるニコチン性アセチルコリン受容体の発現増加 - 山村, 彩; 中浜, 光哉; Hossain, Alamgir; 北村, 文也; 高橋, 理恵; 山村, 寿男; 佐藤, 元彦 (日本薬理学会年会要旨集, 2022)
Smoking causes hypoxic vasospasm, thickening, and inflammation. Such responses are similar to the pathological mechanism of pulmonary arterial hypertension (PAH). PAH is a progressive and fatal disease that is characterized by the irreversible remodeling of the pulmonary artery. Pulmonary vasospasm, thickening, and inflammation are triggered by a chronic increase in cytosolic Ca2+ concentration. Here, we focused on the expression of nicotinic acetylcholine receptors (nAChRs), which are associated with cytosolic Ca2+ signaling, in PAH and hypoxic stress. The expression of the α subunits of nAChRs in pulmonary arterial smooth muscle cells (PASMCs) from normal subjects and idiopathic pulmonary arterial hypertension (IPAH) patients was analyzed by RT-PCR. Normal-PASMCs expressed nAChRα5 and α9 subunits. On the other hand, IPAH-PASMCs expressed nAChRα1, α5, and α7 subunits. As a result of Western blotting, the expression of nAChRα1and α7 proteins was upregulated in IPAH-PASMCs. In addition, the expression of nAChRα1 subunits was also increased in PASMCs from monocrotaline-induced pulmonary hypertensive rats. Furthermore, hypoxic exposure (1% O2) increased nAChRα7 expression in normal-PASMCs. In conclusion, the expression of nAChRα1 and α7 subunits is upregulated in chronic respiratory diseases including PAH and hypoxic stress.